(untitled) (Texas Journal of Medical Science, 2022)
Endoprosthetics of the joints of the lower limb is a very traumatic intervention. The relevance of this issue is due to the intensive development and introduction of the latest technologies in modern surgical interventions, including joint replacement, and a significant expansion of indications for surgical treatment. In connection with the above, anesthesia should correspond to the nature of this intervention: completely block nociceptive impulses, maximally reduce perioperative blood loss and the need for donor blood components, the likelihood of developing thromboembolic complications in the postoperative period, and the severity of postoperative pain syndrome